Найдавніший кам’яний якір з поселення Грибівка ІV - Іванова, С.В.; Петрова, К.А.; Будикін, І.А. (Археологія, 2003)
У статті розглянуто кам'яний якір та вироби з глини із поселення Грибівка IV у Північно-Західному Причорномор'ї. В статье рассмотрен якорный камень из поселения сабатиновской культуры в Северо-Западном Причерноморье. Приведены аналогичные находки бронзового века из других территорий, предпринята попытка реконструкции формы якоря.
Находка якоря на поселении сочетается с другой редкой категорией находок — «глиняными яйцами». Находки сопоставлены на семантическом уровне. The article deals with anchor stone from the settlement of Sabatynivs’ka culture in the northwestern area of the territory to the North from the Black Sea coast. The authors adduce analogous of finds which dates to the Bronze Age from another territories, and make the attempt of reconstruction of shape of an anchor.
Finding of the anchor on the settlement is brought into correlation with another rare category of finds, the «clay eggs» are. The finds were compared by semantic method.